2017
DOI: 10.1016/j.jconrel.2017.03.387
|View full text |Cite
|
Sign up to set email alerts
|

Sequence segregation improves non-covalent protein delivery

Abstract: The impermeability of the plasma membrane towards large, hydrophilic biomolecules is a major obstacle in their use and development against intracellular targets. To overcome such limitations, protein transduction domains (PTDs) have been used as protein carriers, however they often require covalent fusion to the protein for efficient delivery. In an effort to develop more efficient and versatile biological vehicles, a series of PTD-inspired polyoxanorbornene-based synthetic mimics with identical chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 40 publications
2
87
0
Order By: Relevance
“…The Tew group has previously shown that precise optimization of the hydrophobic domain led to enhancements in siRNA delivery to a non‐trivial target, Jurkat T cells, while the presence of a hydrophobic block boosted EGFP delivery to HeLa cells . Varying the segregation of the hydrophobic domain has also been shown to impact EGFP binding and delivery . Since Tew and coworkers have demonstrated that the likely and prevalent mode of internalization for these ROMP‐based PTDMs is endosomal uptake and given that hydrophobicity initiated fusion into the endosomal membrane is a method of escape, further modification of PTDM hydrophobicity could be a mechanistically advantageous way to improve delivery.…”
Section: Methodsmentioning
confidence: 99%
“…The Tew group has previously shown that precise optimization of the hydrophobic domain led to enhancements in siRNA delivery to a non‐trivial target, Jurkat T cells, while the presence of a hydrophobic block boosted EGFP delivery to HeLa cells . Varying the segregation of the hydrophobic domain has also been shown to impact EGFP binding and delivery . Since Tew and coworkers have demonstrated that the likely and prevalent mode of internalization for these ROMP‐based PTDMs is endosomal uptake and given that hydrophobicity initiated fusion into the endosomal membrane is a method of escape, further modification of PTDM hydrophobicity could be a mechanistically advantageous way to improve delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has developed and studied PTDMs capable of non‐covalently binding and delivering protein cargo into difficult‐to‐transfect cell lines . Most of this work has centered on chemically optimizing PTDMs through structure–activity relationships, and special attention has been given to optimizing the ratio of hydrophilic to hydrophobic monomers and the overall polymer hydrophobicity (Figure ) . Some of these same studies have featured cursory explorations of how polymer–protein binding impacts intracellular delivery.…”
Section: Polymer‐protein Binding Equilibrium and Deliverymentioning
confidence: 99%
“…In this sense, it is quite possible that binding affinity could be correlated to the activity or bioavailability of the cargo in the intracellular environment. Questions surrounding cargo function and bioavailability post‐delivery are usually answered by delivering enzymes or other functional proteins and monitoring said function . In a separate body of non‐delivery‐related work, polymer–enzyme binding was studied with respect to turning enzyme function on and off .…”
Section: Correlating Binding With the Intracellular Activity Of Bioacmentioning
confidence: 99%
See 2 more Smart Citations